Analysis of Facial Information for Healthcare Applications: A Survey on Computer Vision-Based Approaches - Marco Leo; Pierluigi Carcagnì; Pier Luigi Mazzeo; Paolo Spagnolo; Dario Cazzato; Cosimo Distante (Information, 2020)
This paper gives an overview of the cutting-edge approaches that perform facial cue analysis in the healthcare area. The document is not limited to global face analysis but it also concentrates on methods related to local cues (e.g., the eyes). A research taxonomy is introduced by dividing the face in its main features: eyes, mouth, muscles, skin, and shape. For each facial feature, the computer vision-based tasks aiming at analyzing it and the related healthcare goals that could be pursued are detailed.